Een mediapark in Brussel? De mediasector en zijn regionale dynamiek - Marlen Komorowski; Victor Wiard; Sabri Derinöz; Ike Picone; David Domingo; Geoffroy Patriarche (Brussels Studies)
This synopsis analyses from a media cluster perspective the characteristics of the media industry in Brussels and assesses the implications for the major policy intervention of the Brussels Capital Region in this industry: the mediapark.brussels, a 10-year urban and property development project at Reyers around the existing site of the public broadcasting companies VRT and RTBF. Our research results shed light on several clustering configurations in the Brussels media industry, highlight the diversity of the media workforce, and offer an overview of different models and activities of worker communities. The current policy framework for the mediapark.brussels project is outlined. The insights gained are used to assess the possible strategies for the project, considering that in Belgium, the media are a competence of the Communities and not of the Government of the Brussels Capital Region. We discuss the tension that manifests itself in the development of mediapark.brussels: tension between an urban and a cultural development, tension between local and international perspective, and tension between a wide-spectrum and a specialised media cluster.